Rotation of PRODAN in excited state - Tomin, Vladimir I. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2006)
Instant spectra and anisotropy kinetics of PRODAN luminescence in different ranges of spectra has been studied upon excitation by picosecond pulses. Instant spectra of luminescence reveal time dependent Stokes shift having intermolecular nature as its characteristic time correlates with dielectric relaxation time of solvent. The mean Brownian rotation time for the curves obtained shows complex character of spectral dependence with maximum ~39 ns near maximum of luminescence intensity and drops down to 15 ns on the edges of the spectrum. An explanation is based on a treatment of intermolecular energy conversion into thermal movement of molecules during relaxation in excited state. Calculations using hydrodynamic model show “stick” boundary conditions for solutes: rotational volumes correspond to solute together with molecules of the first coordinative sphere filled by solvent.
Optica Applicata, Vol. 36, 2006, nr 4, s. 523-528
Keywords: optyka; PRODAN; luminescence; rotation; excited state; charge transfer states; conformers; relaxation